2020
DOI: 10.3390/ijms21093089
|View full text |Cite
|
Sign up to set email alerts
|

Possible Relevance of PNPLA3 and TLL1 Gene Polymorphisms to the Efficacy of PEG-IFN Therapy for HBV-Infected Patients

Abstract: Lifestyle changes have led to an increase in the number of patients with nonalcoholic fatty liver disease (NAFLD). However, the effects of NAFLD-associated single-nucleotide gene polymorphisms (SNPs) in HBV-infected patients have not been adequately investigated. Methods: We investigated the association of the NAFLD-related SNPs patatin-like phospholipase domain-containing protein 3 (PNPLA3; rs738409), transmembrane 6 superfamily member 2 (TM6SF2; rs58542926), 17-beta hydroxysteroid dehydrogenase 13 (HSD17B13;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…TLL1 rs17047200 SNP may produce catalytically highly active short isoform (TLL1 isoform 2) [16]. Of note, we evaluated a SNP of Tolloid Like-1 (TLL-1) as a complementary activating protease and also as potentially able to stimulate the spike protein of SARS-CoV-2 [17].…”
Section: Introductionmentioning
confidence: 99%
“…TLL1 rs17047200 SNP may produce catalytically highly active short isoform (TLL1 isoform 2) [16]. Of note, we evaluated a SNP of Tolloid Like-1 (TLL-1) as a complementary activating protease and also as potentially able to stimulate the spike protein of SARS-CoV-2 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that response-guided therapy or early on-treatment HBV RNA levels could be of great help in the management of patients treated with PegIFNα, 29 , 31 while it is unclear which indicators can predict that patients with CHB could benefit from earlier treatment. Although several SNPs have been proposed, 8 , 32 , 33 the effect of GNLY rs11127 on PegIFNα efficacy has never been reported before. Previously, GNLY rs11127 was regarded as an important factor in HBV clearance in patients infected with HBV in a Korean study.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, predictive models of the efficacy for initial treatment with PegIFN were mainly reported on studies of some clinical baseline indicators 34 or SNPs. 32 , 33 , 35 Therefore, we compared the performance of clinical variables combined with PGS and that of clinical variables only, in predicting PegIFNα efficacy. The results demonstrated that the performance of the model including clinical variables combined with PGS in predicting PegIFNα efficacy was remarkably improved compared to that of the model including clinical variables only.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme can also activate SARS-CoV-2 S glycoprotein. rs17047200 (AA genotype) [19,212]. No data reported.…”
Section: Tll1mentioning
confidence: 99%